Digitalisasi Pemasaran dan Implementasi Mesin Spinner untuk Meningkatkan Penjualan Produk Bandeng Yuwono - Cinderatama, Toga Aldila; Alhamri, Rinanza Zulmy; Widyastuti, Ratna; Wahyu, Mujahid; Yanuarmawan, Dion; Hamidah, Fitria Nur (Universitas Nusantara PGRI Kediri, 2025)
Bandeng Presto Duri Lunak Bu Yuwono is a micro, small, and medium enterprise (MSME) located in Mojoroto, Kediri, East Java, established in 1999 with three family-member employees. The business markets its products from morning until noon, followed by sourcing ingredients for the next production cycle. A situational analysis identified several challenges, including traditional marketing methods, manual transaction recording, conventional production tools, and limited knowledge and skills in information technology utilization. To address these issues, the Service Team implemented a series of steps: preparation, development of an e-commerce website, creation of a transaction recording module, production of an oil-draining spinner, technology training for the partner, and program evaluation. This initiative resulted in an e-commerce website and transaction recording module at bandengyuwono.id, an oil-draining spinner machine, and technology training, bringing economic benefits through an expanded marketing reach, increased production, and improved profitability for the partner.